1989
DOI: 10.1097/00000658-198912000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Chest Injuries in Childhood

Abstract: Differences in anatomy and mechanisms of injury are believed to contribute to the unique response of children to thoracic trauma. To characterize the scope and consequences of childhood chest injury, we reviewed the records of 105 children (ages 1 month to 17 years, mean 7.6 years) with chest injuries admitted to a level I pediatric trauma center from 1981 to 1988. Nearly all injuries (97.1%) were due to blunt trauma, and more than 50% were traffic related. Rib fractures, commonly multiple, and pulmonary contu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
80
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(83 citation statements)
references
References 11 publications
0
80
0
3
Order By: Relevance
“…[5] Paediatric blunt thoracic trauma presents difficulties in both diagnosis and management owing to differences in anatomy. [6] Initial investigations may not reveal significant axial skeletal damage despite high energy transfer and resultant lung contusion, because of the elastic nature of the child's chest wall. Associated injuries such as rib and sternal fractures are thought to occur less commonly in the paediatric population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Paediatric blunt thoracic trauma presents difficulties in both diagnosis and management owing to differences in anatomy. [6] Initial investigations may not reveal significant axial skeletal damage despite high energy transfer and resultant lung contusion, because of the elastic nature of the child's chest wall. Associated injuries such as rib and sternal fractures are thought to occur less commonly in the paediatric population.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] We aimed to review and contrast the incidence and outcome of blunt thoracic trauma among adults and children in a single level I trauma centre over a 6-year period.…”
mentioning
confidence: 99%
“…Ismail and Al-Refaie (2012) found the rates for these two types of trauma to be 2.1% and 97.9%, respectively. In terms of the most common cause of blunt traumas as out-of-vehicle traffic accidents, Nakayama et al (1989) and Ismail and Al-Refaie (2012) reported rates of 25.7% and 38.3%, respectively, for this type of trauma. Meller et al (1984) found that penetrating thoracic traumas were seen less in children compared to adults, being most commonly seen in late childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama et al (1989) evaluated thoracic traumas in patients under 17 years old and found that the rate of penetrating traumas was 2.9% and of blunt traumas was 97.1%. Ismail and Al-Refaie (2012) found the rates for these two types of trauma to be 2.1% and 97.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation